Dogmatic Theology in Bulgaria during the 20th Century (Forum Theologicum Sardicense, 2025)
The author provides a brief review of research in Dogmatic Theology in Bulgaria from the late 19th century to the early 21st century. He outlines the key scholars in this field and their most notable research programs. Additionally, the author seeks to identify the main characteristics of Orthodox Dogmatic research in Bulgaria during this period, considering the specific historical circumstances. While not offering a comprehensive overview, he addresses some of the most complex questions faced by Bulgarian researchers in Dogmatics and proposes potential solutions for the revitalization of this field in Bulgaria.
Keywords: Dogmatic Theology; Systematic Theology; Bulgarian Theology